Plaque index differences before and after teeth brushing with and without propolis dentifrice - Iswari, Allin Perama; Riyanti, Eriska; Hadidjah, Dede (Universitas Padjadjaran, 2010)
Dentifrices used to aid plaque removal from dental surfaces and gums while teeth brushing. Propolis is one of bee products that can be added into dentifrices and its property is to inhibit plaque-forming bacteria growth. The main objective of this study was to rule out any plaque index differences before and after teeth brushing with and without propolis contained dentifrices. It was a quasi-experimental research with the single blind-parallel method. Subjects were 30 students from 33 Junior High School Bandung aged 11-13 years old, collected by purposive sampling technique. Subjects divided into groups which using propolis and without propolis dentifrices, teeth brushing. The plaque was assessed using the Patient Hygiene Performance (PHP) Index from Podsadley and Haley. Data collected would be tested using the paired t-test and independent t-test. This study concluded that there was a difference of plaque index before and after teeth brushing with and without propolis contained dentifrice. Indeed, the propolis contained dentifrice less much decrease the plaque index compared to the without propolis contained dentifrice.